Propuesta para el rescate de la entidad de la fiesta religiosa del 7 de octubre en honor a la Virgen del Rosario de la parroquia Gualel del cantón Loja - Castillo Aguilera, Vanessa Tatiana (2016)
As students of the National University of Loja, of the Juridical Social and Administrative Area of the Career of Engineering in Tourist Administration, there exists the need to know and reach with the tourist development of our environment, for which makes to itself present this project that has as aim, to investigate, to know and to analyze all the compiled information brings over of the religious holiday of October 7 in honor the Virgin of the Rosario of the parish Gualel, of the canton Loja. It is for it that appears the need to present the work called " Offer for the Rescue of the Identity of the Religious Holiday of October 7 in honor to the Virgin of the Rosario of the parish Gualel of the canton Loja ", with which it is tried to contribute to the promotion and visits to this festivity that will allow to obtain economic income for the sector, improving the quality of life of his inhabitants. For the accomplishment of the present project, we have the aims since it is to contribute to the development of the Cultural Tourism of the parish Gualel across the rescue of the identity of the principal holiday, where information was compiled brings over of the festivity and in addition there was done the analysis of the historical reality and certification of the religious holiday in honor to the Virgin of the Rosario, where it was detailed it brings over of the production of the same one. Inside the methods and technologies that one used in this work we have the bibliographical method that allowed the summary of the principal information of the festivity of the parish, complementing it with the historical method that linked with the revelation of the concrete history, the principal stages of the development of this holiday that allowed the deepest knowledge of this celebrity likewise with the technology of the interview the one that helped to obtain the compilation and storage of information of the involved principal ones and inhabitants of the holiday. Besides there was realized the analysis FODA, where that recorded a series of information relating to the topic to investigating and simultaneously across the same one there realized a counterfoil high FODA impact that gave like proved the strategies for the rescue of the identity of the parish together with the analysis of considered FODA that allowed to bear in mind the degree of the problem and his fortresses of the parish. In turn with the second aim that is to propose alternatives for the rescue of the cultural identity of the parish Gualel, there was in use the analytical method that helped to analyze relevant strategies for the rescue of the customs and traditions that one comes giving in this parish; likewise across the technology of the observation it was possible to visualize widely on the needs of the sector, as well as of the routes that it is necessary to to bear in mind for the rescue of the religious holiday of October 7 in honor to the Virgin of the Rosario of the parish Gualel. Finally for the third aim that is validar the information obtained of the study with the principal ones involved to emphasize the cultural wealth realized a socialization, where across a verbal and visual exhibition it started itself knowing the importance that has the traditional religious holiday of October 7 in honor to the Virgin of the Rosario of the parish Gualel. With the culmination of the aims raised across strategies that will be applied correctly, it came near to the conclusion that is necessary to rescue the cultural ancient heritage of the parish Gualel since this one possesses an identity that been the legacy of his forbears, and inside these there exist customs and traditions that one comes giving every year in the accomplishment of the holidays, which will help to the identification of customs and own local traditions. As recommendations, to the Parochial Meeting it is suggested to take charge of the rescue of the cultural heritage and to the basic organizer of the holiday the parson must take corresponding measurements to avoid the alcoholism and one does not lose the customs and traditions of the parish Gualel where the tourists could have the opportunity to estimate and know the cultural identity of the same one.